The politics of critique: On the socio-politically engaged dimension of Foucault's methodology - Urošević Milan (Srpska Politička Misao)
It seems that the work of Michel Foucault has, in the last decade, attracted some attention. This attention is a result of media engaging in a sensationalist way with his work and his private life. He is usually being portrayed as a radical postmodern nihilist, while his work is being blamed for inspiring contemporary identity politics and the practice of political correctness. These developments seem to us as a good reason to go back to Foucault's work. Since the relation between scientific work and social engagement is an important problem in contemporary social sciences and humanities, we decided to research the way Foucault conceptualized the relation between his intellectual work and his political activism. We begin our paper by elaborating some of the most important theoretical concepts in Foucault's work. We start from his notion of practice, as a form of social action, and then move on to the two types of practices Foucault distinguishes: discursive and non-discursive practices. In the end of this chapter, we present the notion of the "dispositive", which Foucault defines as an interconnected system of discursive and non-discursive practices, and his notion of subjectivity, which is defined as a relation an individual has with himself. In the next chapter we engage with methodologies Foucault uses in his research. We start with archeology, a methodology he used in the beginning of his work, while researching discursive practices. We then move on to genealogy, which is a methodology Foucault used to study systems that combine discursive and non-discursive practices. Since genealogy is the methodology, he envisions as being connected to political practice, we will especially focus on it. Precisely in the next chapter of our paper we will investigate the ways in which Foucault conceptualizes the relationship between genealogical research and political activism. We will show that he sees political activism as a primary criterion for choosing a research subject. Genealogical research then, for Foucault, provides a reflection on the history of an institution, around which the political struggle in question is waged. The results of the genealogical research are, for him, suppose to show how the institution in question is a product of contingent historical processes and, therefore, can be changed through political action, since it is not grounded in any metaphysical necessity. In the last chapter of our analysis, we will deal with Foucault's attempt to connect his genealogical research and political activism through an ethical framework. In this chapter we will present his concept of enlightenment, as an ethical tradition in which both his intellectual and political work can be situated. He conceptualizes the enlightenment as an "attitude", which consist of various kinds of practices, through which an individual constantly tests and transgresses existing boundaries, which are imposed on our actions and forms of subjectivity. Therefore, through these practices the individual, by his very existence, shows that those boundaries are contingent, and can be changed. In the conclusion our paper we, again, turn to contemporary characterizations of Foucault's work. We show that our elaboration of his ideas proves those characterization as inadequate and wrong.